2018
DOI: 10.4018/ijdldc.2018010102
|View full text |Cite
|
Sign up to set email alerts
|

Computer Use Skills of Undergraduate Students in Bells University of Technology, OTA

Abstract: Thecontinuousadoptionanduseoftechnologyineducationhasnecessitatedtheneedforcomputer useskillstoallstakeholdersintheeducationalsector.Apparently,educationinthepresentageis characterizedbytheadoptionanduseoftechnology.BellsUniversityofTechnology,Ota,isaprivate institutionthathavedemonstratedtheuseoftechnologyinteaching,learningandresearchprocesses. Thisworkistherebyaimedatdeterminingstudents'abilitytouseeducationaltechnologiesusing BellsUniversityofTechnologyasacasestudy.Astructuredquestionnairewasadoptedandused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Furthermore, we found that information-seeking behaviors, IT skills, age, and gender all had a positive impact on academic performance. Similarly, another study advised that students seeking entry to the Bells University of Technology receive hands-on computer training sessions (Oshilalu and Emiri, 2018). At the same time, research showed that ICT literacy standards significantly correlate with academic performance in Arts and Social Sciences, Health Science, Management Science, and Science and Technology e-learners, but not in Agriculture, Education, or Law e-learners (Aboderin, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found that information-seeking behaviors, IT skills, age, and gender all had a positive impact on academic performance. Similarly, another study advised that students seeking entry to the Bells University of Technology receive hands-on computer training sessions (Oshilalu and Emiri, 2018). At the same time, research showed that ICT literacy standards significantly correlate with academic performance in Arts and Social Sciences, Health Science, Management Science, and Science and Technology e-learners, but not in Agriculture, Education, or Law e-learners (Aboderin, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Using the Bells University of Technology as a case study, an analysis was conducted to determine the ability of students to use educational technologies. Their results showed that the computing capacity of a large number of newly enrolled students (75 percent) is marginal, which would hurt their ability to deal with a computerized educational environment (Oshilalu and Emiri, 2018). Since students can access information anytime and from any place, ICT allows for greater consistency in education delivery (Johari et al, 2020).…”
Section: It Skillsmentioning
confidence: 99%